Empowering Farmers in Lagan Ulu Village through the Irrigation Water Use Improvement Acceleration Program (P3-TGAI) : Pemberdayaan Petani di Desa Lagan Ulu melalui Program Percepatan Peningkatan Tata Guna Air Irigasi (P3-TGAI) - Saputra, Rido; Aswandi, Aswandi; Indriyani, Indriyani; Fortuna, Dewi; Daulay, Diana Pebriani; Viyona, Melvi; Rohman, Fatkhul; Rasinta, Igef (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
The agricultural sector in Lagan Ulu Village faces productivity challenges due to irrigation damage and the absence of a management institution. This community service project aims to establish a Water User Farmers Association (P3A) and increase farmer capacity through the Irrigation Water Use Improvement Acceleration Program (P3-TGAI). The activity took place from July to September 2025 and used a participatory approach involving farmers, village officials, lecturers, and 10 KKNT students. The program stages included problem identification, outreach, deliberations with 17 core representatives of farmer groups, preparation of Articles of Association/Bylaws (AD/ART) and the Budget Work Plan (RKA), legalization, and monitoring and evaluation. As a result, a formal organization, "Lagan Ulu Berjaya Water Users Farmers Association," was successfully established and legalized through a notarial deed. The AD/ART and RKA documents now serve as operational guidelines that regulate the water management system, fees, and sanctions. Evaluation using a standard observation sheet indicated the program's success with a global score of 4.00 (High category). The sense of ownership and active cooperation indicators achieved a maximum score of 5.00, whereas the mechanical capacity for independent floodgate maintenance remained limited (3.00). Overall, this institutional strengthening successfully transformed water governance from an individualistic to a systematic approach, supporting the sustainable irrigation of 210 hectares of tidal land in Lagan Ulu Village.